2019
DOI: 10.3390/agronomy9110717
|View full text |Cite
|
Sign up to set email alerts
|

Key Aspects on the Biology, Ecology and Impacts of Johnsongrass [Sorghum halepense (L.) Pers] and the Role of Glyphosate and Non-Chemical Alternative Practices for the Management of This Weed in Europe

Abstract: Sorghum halepense (L.) Pers is a common and noxious worldwide weed of increasing distribution in many European countries. In the present review, information on the biology, ecology, agricultural, economic and environmental impact of johnsongrass is given, and the current status of this weed in Europe is discussed. Furthermore, special attention is given to the important role of field trials using glyphosate to control weeds in arable and perennial crops in many European countries. Some of the factors which aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 62 publications
(57 reference statements)
1
23
0
2
Order By: Relevance
“…This applies also for other nonchemical control methods such as mowing. Although two mowing passes were not effective in this site, repeated and frequent mowing controls S. halepense seedlings and reduces rhizome growth and shoot regrowth after clipping (Travlos et al 2019;Warwick and Black 1983). For instance, mowing S. halepense at the ground surface every 2 wk from spring to autumn caused significant reductions on S. halepense dry weight and rhizome length in early studies (Horowitz 1972).…”
Section: Weed Control In the Vineyardmentioning
confidence: 86%
See 2 more Smart Citations
“…This applies also for other nonchemical control methods such as mowing. Although two mowing passes were not effective in this site, repeated and frequent mowing controls S. halepense seedlings and reduces rhizome growth and shoot regrowth after clipping (Travlos et al 2019;Warwick and Black 1983). For instance, mowing S. halepense at the ground surface every 2 wk from spring to autumn caused significant reductions on S. halepense dry weight and rhizome length in early studies (Horowitz 1972).…”
Section: Weed Control In the Vineyardmentioning
confidence: 86%
“…The need to optimize integrated management systems to eradicate S. halepense is further supported by cases reporting the presence of S. halepense accessions with resistance to selective herbicides and glyphosate in the perennial orchards of the Mediterranean zone (Heap 2021;Vazquez-Garcia et al 2020). To maintain efficacy over time, timely herbicide applications should be combined with cultural practices such as mowing (Travlos et al 2019). Such systems have been reported to provide sufficient control of perennial rhizomatous weed species that are troublesome in perennial crops (Raimondi et al 2020).…”
Section: Weed Control In the Vineyardmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have recently shown resistance of Johnsongrass to ALS-inhibitors and new problems in the control of this troublesome weed have arisen (Malidža, 2015). The most efficient herbicide for Johnsongrass control is glyphosate (Travlos et al, 2019). Maize infestation with Johnsongrass and its complex control is one of the reasons for the development of Roundup Ready technology (Ferrell & Witt, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Successful control of Johnsongrass has to be based on the integrated application of preventive, mechanical, physical, chemical, biological and other measures (Simić et al, 2020;Travlos et al, 2019). Combined application of different cropping practices can facilitate optimal crop productivity, since repetitive application of the same measures in agricultural practice leads to disturbances in the agro-ecosystem (Liebman & Staver, 2001).…”
Section: Introductionmentioning
confidence: 99%